Repetitive process based design of PD-type iterative learning control laws for batch processes with time-delays - Maniarski, Robert; Paszke, Wojciech (1975- ); Rogers, Eric; Tao, Hongfeng
This paper uses linear matrix inequality (LMI) techniques to design an iterative learning control (ILC) law or a class of batch processes with state delays. The design procedure uses the stability theory for repetitive processes, where the design problem is first converted into one for a parallel interconnection of repetitive processes with delays. This setting allows the computation of the PD-type control law gain matrices, and the Kalman-Yakubovich-Popov (KYP) lemma ensures batch-to-batch error convergence over the complete frequency domain. A numerical example illustrates the paper developments and proves that the design is effective and brings some advantages when compared to the existing alternatives.
Keywords: PD-type iterative learning control; delayed systems; linear matrix inequality; batch processes